Single track coincidence measurements of fluorescent and plastic nuclear track detectors in therapeutic carbon beams - Osinga-Blättermann, Julia-Maria; Ambrožová, Iva; Pachnerová Brabcová, Kateřina; Akselrod, Mark S.; Jäkel, Oliver; Davídková, Marie; Greilich, Steffen (Journal of Instrumentation, 2014)
In this paper we present a method for single track coincidence measurements using two different track detector materials. We employed plastic and fluorescent nuclear track detectors (PNTDs and FNTDs) in the entrance channel of a monoenergetic carbon ion beam covering the therapeutic energy range from 80 to 425 MeV/u.
Gesehen am 08.09.2020